MOVEMENT OF MENTAL REVOLUTION WITHIN NURSING PERFORMANCE IN GIVING NURSING CARE AT RSUD JEMBER - Asmuji asmuji (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
Abstract: Nursing resource has been come to dominate the number of other human resources in health care.. However there was biased news about nursing performances in giving nursing care. Mental revolution in public health services was hoped it could make the personal inside will have character with higher integrity, good work ethic that focused on professionalism, independent, creative, innovative, and be a life-long learners. Purpose: to analyze the relationship between educational level, work period, nurse’s perception about mental revolution in giving nursing care. Methods: Design of this research was correlation. The research population was all nurses at inpatient room with 40 nurses as sample who spread out over 4 rooms that taken by simple random sampling. Questionnaire was used in this research as collecting data instrument and spearman rho with α= 0.05 was used to see the correlation between both of the variables. Result: The result of this research showed: 1) no relationship were note between education level of respondent and their performance in giving nursing care (p= 0.702; α= 0.05; r= -0.063), 2) no relationship were noted between variable of respondent’s work period and their performance in giving nursing care (p= 0.447; α= 0.05; r= - 0.124); 3) the relationship noted between perception variable about movement of mental revolution and their performance in giving nursing care (p= 0.028; α= 0,05; r= 0.348). Conclusion: Therefore the relationships noted between perception variable about movement of mental revolution and their performance in giving nursing care. Monitoring and evaluation periodically on performance of their nurses, trying to evaluate performance of nurses/ employees through 360O model, such as combination between self-evaluation, manager evaluation, peer- evaluation, and user evaluation. Keywords: Mental Revolution, Nursing Performance, Nursing Care